(Pre-)Scripted Creativity: An Examination of the Creativity Movement in Spain's Contemporary Music Education Literature - Antía González-Ben (Universidade de Lisboa, 2015)
Creativity is a pervasive topic in current discourses on music education inSpain. Creativity is commonly seen as universal. Also, the construct is oftenseen as entirely positive and as a desirable personality trait. This paper challengesthese premises. It unpacks creativity's contingency as a cultural constructattached to a particular set of ideas and values, and it examines thisnotion as part of a particular regime of truth. The paper begins by contextualizingthe Spanish creativity movement within music education and bydelineating the socio-political and economic coordinates that surrounded itsemergence in contemporary Spain. Then, the paper approaches creativity asa pedagogical object, and it explores this construct's ambivalent associationwith long-standing tropes about curriculum design and the social role ofeducation. Discourses on creativity in Spanish music education ultimatelycontribute to the fabrication of an ideal type of student and, by extension,to the «creation» of a particular kind of Spanish citizen. The paper ends byexamining potential dissonances between creativity's hoped-for outcomesand its actual effects.